A Novel Approach for Segmentation of Brain Image using a Multiscale Transform and a Region Based Active Contour - Ullal, Smitha P; C P, Dr.Nanjraj; Meera A, Dr. (British Journal of Healthcare and Medical Research, 2019)
Over the Past decade Medical Image segmentation is one of the most challenging and focused topic for intensive research in interdisciplinary areas of Image processing and computer vision. Segmentation is the process of automatic or semi-automatic detection of boundaries [5]. In this paper, we implement a novel unsupervised method for segmenting MRI brain Images based on multiresolution transforms and region based active contour. Application of multiscale, multiresolution methods with active contour is most interesting research topic in image segmentation [6].This new application makes segmentation algorithms more economical for computation.